Validation of the Quantitative Determination Method of the active substance in Angiolin eye drops by spectrophotometry - Kucherenko, L. I.; Akopian, R. R.; Portna, О. О.; Derevianko, N. V.; Skoryna, D. Yu.; Кучеренко, Людмила Іванівна; Акопян, Ріма Романосівна; Портна, Олена Олексіївна; Дерев'янко, Наталя Вікторівна; Скорина, Дмитро Юрійович (My University, 2024)
Today, cataracts are the main cause of vision loss. Therefore, the creation of new ophthalmic medicines (drugs), namely eye drops, based on the active substance angiolin ((S)-2,6-diaminohexanoic acid 3-methyl-1,2,4-triazolyl-5-thioacetate) is an urgent task. Previously, we developed a method of standardization of the active substance – by the spectrophotometry. According to the requirements of the SPhU, the next step was the validation of the developed methods. That became the purpose of our work. Validation of the method of quantitative determination of active substances was carried out according to the following indicators: specificity, linearity, range of application, accuracy, correctness and robustness. In the course of the conducted studies, it was established that the method is characterized by sufficient convergence and correctness, as the criterion of insignificance of the systematic error of the method is fulfilled. The systematic error of the method satisfies the requirements of statistical and practical insignificance. The high value of the correlation coefficient r = 1.0000 and 0.99994 satisfies the requirements of the acceptance criterion (r = 0.9998) and confirms the linearity of the dependence between the amount of Angiolin taken and found in the range from 80% to 120%, according to its nominal content in the drug. The requirements for the linear dependence parameters (a, SD0/b, r) of the Angiolin determination method are met in the entire concentration range from 80% to 120% of the nominal value. Thus, the developed method of standardization of active substances in Angiolin eye drops is valid and can be introduced into the project of QCM (quality control methods).
Keywords: Angiolin; Eye Drops; Quantitative Determination; Spectrophotometry; Validation